LOCAL LANGUAGES’ EXISTENCE IN THE FOURTH INDUSTRIAL REVOLUTION ERA: A SURVEY ON EFL STUDENTS (KEBERADAAN BAHASA DAERAH DI ERA REVOLUSI INDUSTRI KEEMPAT: SEBUAH SURVEY PADA MAHASISWA EFL) - Yulitriana Yulitriana; Akhmad Fauzan; Lesly Martha Cecylia Meka; Kristiani Natalina (Jurnal Gramatika, 2022)
Previous studies have investigated the community's perspectives on local languages’ existence due to exposures to various languages in residential areas or through formal education in secondary schools. However, there is a lack of evidence on the research of university students’ perspectives on local languages’ existence because they are exposed to international languages as a result of learning and the vast development of technology. Therefore, the current study investigates English as a Foreign Language (EFL) students' beliefs on local languages' existence in the era of the Fourth Industrial Revolution. In order to measure intangibles, survey research with a one-shot design was conducted following the techniques of planning, defining the population, sampling, constructing the instrument, conducting the survey, and processing the data. The participants of this study were university students majoring in English Language Education and the setting of this study was at one public university in Central Kalimantan Province of Indonesia. A questionnaire in the open- and close-ended questions was distributed to collect data. The current study results confirm that the majority of the participants were active users of local languages and were exposed to international languages (English, Korean, Japanese) through education and entertainment. The participants positively viewed the local languages' existence amidst the exposure of international languages because the local languages were still used in daily life and parts of culture that had been inherited for generations. Furthermore, the participants had taken action to preserve their local languages by continuously using local languages in their family and friendship domains both in the real world and through social media.